INTERNAL CONTROL ANALYSIS OF SALES AT PT. ASIA'S GROWTH - Farida Sagala; Arthur Simanjuntak; Lamria Sagala; Mitha Christina Ginting (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
The purpose of this research is to find out how the implementation of internal sales control runs effectively and efficiently. Claims internal control is very important so that claims are received on time. PT. Growth Asia is a foundry company. Documentation & interviews are used as data collection methods. The research method used in this study is a qualitative narrative. Analytical technology uses data reduction techniques, data visualization, and data verification. The results of the study show that the internal control component in sales control is effective because the internal control component already exists in the company and the credit limit applies. The results of this study also indicate that the internal control of accounts receivable is quite effective in terms of a clear division of labor, where more than one department handles receivable collection. sales level of PT. Asian growth picked up from 2020-2021, showing that internal sales controls are working effectively.